2011
DOI: 10.1097/mbc.0b013e328343f8eb
|View full text |Cite
|
Sign up to set email alerts
|

Hemorrhagic manifestation of megaloblastic anemia: report of two cases and literature review

Abstract: Megaloblastic anemia is not uncommon in developing countries. Its presentation as thrombocytopenia and hemorrhagic manifestation are, however, rare. We describe the clinical scenario in two young patients who presented to the emergency room of Sir Ganga Ram Hospital, a tertiary care center in New Delhi, India, with pancytopenia and bleeding diathesis. Both patients improved after B12 supplementation. Reports of two cases and a brief review is presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…There are many studies and case reports regarding vitamin b12 deficiency with thrombocytopenia and bleeding manifestations. [21][22][23][24] However few studies did found thrombocytopenia in patients with vitamin b12 deficiency but it was not significantly associated. 25,26 Marwaha RK, et al reported 10 children with megaloblastic anemia and a hemorrhagic diathesis .…”
Section: Discussionmentioning
confidence: 99%
“…There are many studies and case reports regarding vitamin b12 deficiency with thrombocytopenia and bleeding manifestations. [21][22][23][24] However few studies did found thrombocytopenia in patients with vitamin b12 deficiency but it was not significantly associated. 25,26 Marwaha RK, et al reported 10 children with megaloblastic anemia and a hemorrhagic diathesis .…”
Section: Discussionmentioning
confidence: 99%
“…Hemorrhagic events such as retinal hemorrhages and purpuric spots have been reported in patients with megaloblastic anemia caused by vitamin B12 deficiency. Bleeding in the form of hematemesis, hemoptysis, and even life-threatening bleeding have also been reported [ 11 ]. Interestingly, Saloujin et al reported that, in cases of megaloblastic anemia caused by vitamin B12 deficiency, the function of platelets is deteriorated [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…The human body requires folic acid (FA) to produce blood cells, secure cell division, and growth [1,2]. Numerous studies have shown that this vitamin is important in the prevention of neurodegenerative diseases, cancer, and cardiovascular disease (CVD) [3,4].…”
Section: Introductionmentioning
confidence: 99%